Making Silica Gel by Utilizing Candlenut and Palm Oil Shell Ash - Muhammad Azhar Shiddiq; Isti Pudjihastuti (Green Publisher Indonesia, 2021)
Oil palm shell ash which is the result of boiler combustion inindustry has the potential to pollute the environment and have a badimpact in the long term so that special treatment is needed. Thisstudy aims to answer this problem by making silica gel fromhazelnut shell and oil palm shell ash with variations in the type ofacid and the ratio of ash to determine the effect of the type of acidand the ratio of the raw material in the form of ash to moisturecontent and water absorption of silica gel. Oil palm shell ash is usedas the main ingredient because it contains the most SiO2compounds compared to other compounds (reaching 39.78%).Candlenut shell is also used as a raw material for silica gel becauseit contains silica (12.58%). The stages in this research include thepretreatment process of the material by washing and drying thematerial, the combustion process of the main ingredient in thefurnace, the process of making sodium silicate and the synthesisprocess of silica gel. Then proceed with water content analysis,analysis of water absorption by silica gel and characterization byScanning Electron Microscope. The results of this study were thatthe type of acid, the concentration of the acid and the time ofmaturation of the gel had an influence on the moisture content ofthe silica gel and the absorption capacity of the silica gel. The silicagel produced using H2SO4 produced more mass than the silica gelusing HCl.